Formative Evaluation in a Context of Pedagogical Renewal: Practices at the service of success - Valdivia Yábar, Silvia Verónica (2020)
In the context of the Peruvian pedagogical renewal, the appropriation by teachers of the prescribed changes in the evaluation plan requires the dissemination of exemplary practices, since several rigorous investigations show that observing examples can favor the learning of new teaching practices. Therefore, the main objective of this research, which was carried out during the second half of 2017, and is reported in this article, has been to characterize the formative evaluation practices of primary school teachers. The qualitative approach was applied and both ethnographic and case study designs were adopted. Data was collected, first, about the planning of the activity with an interview with13 volunteer teachers; then, on the actions of teachers and students through the filmed observation of 25 learning-teaching activities; finally, about the significant segments of the activity recorded through an interview with the teachers. The spontaneous practices of teachers have been analyzed in their double behavioral and cognitive dimension. The study focused on the different elements of the required processes and the devices implemented; as well as, about the contents treated. The results show that the participants have integrated into their practices many characteristics of the formative evaluation, recommended by the Ministry of Education, and that their main challenge consists in sharing the responsibility of the regulation processes with the student by creating the conditions to develop their ability to self-regulate their learning.